Legislative regulation of public health in Croatia in the second half of the 19th century - Gardaš, Miro; Čandrlić, Slavko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
In the provisions of the 1868 Croatian-Hungarian Settlement, internal administration was seen as one of the autonomous areas that Croatia regulated on its own. Part of that was public health, which had been regulated in a very outdated manner up to that point. Appointing Ivan Mažuranić the Ban of Croatia paved way for substantial reforms in numerous areas of public and social life. Among other reforms, legal regulation of public health was proved to be necessary. In this paper we will attempt to present the legal framework regulating public health in Croatia, as well as use specific examples from the archival fonds of the Croatian State Archives in Osijek to portray how these laws were applied in everyday life.